Unveiling inverted D genes and D-D fusions in human antibody repertoires unlocks novel antibody diversity - Ponraj Prabakaran; Abhinav Gupta; Sambasiva P. Rao; Deepak Rajpal; Maria Wendt; Yu Qiu; Partha S. Chowdhury (Communications Biology)
Abstract Antibodies, essential components of adaptive immunity, derive their remarkable diversity primarily from V(D)J gene rearrangements, particularly within the heavy chain complementarity-determining region 3 (CDR-H3) where D genes play a major role. Traditionally, D genes were thought to recombine only in the forward direction, despite having identical recombination signal sequences (12 base pair spacers) at both ends. This observation led us to question whether these symmetrical sequences might enable bidirectional recombination. We identified 25 unique inverted D genes (InvDs) in both naive and memory B cells from antibody repertoires of 13 healthy donors. These InvDs utilize all three reading frames during translation, producing distinct amino acid profiles enriched in histidine, proline, and lysine in CDR-H3s of antibodies with potential functional diversity. Notably, our analysis revealed a broader range of D-D fusions, including D-D, D-InvD, InvD-D, and InvD-InvD configurations, opening new perspectives for antibody engineering and therapeutic development.